2016
DOI: 10.1177/0267659116662520
|View full text |Cite
|
Sign up to set email alerts
|

Are adjunct subvalvular techniques more effective than isolated restrictive annuloplasty for treating ischemic mitral regurgitation?

Abstract: This review focused on whether subvalvular techniques are more effective than isolated restrictive annuloplasty in addressing ischemic mitral regurgitation (MR). Searching identified 445 papers and, following a selection process, we ended up with 10 articles. Two were propensity-matched studies, four retrospective and four prospective, non-randomized studies. The end points of interest were late recurrence of MR, other early echocardiographic outcomes of mitral function and early mortality. All studies focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Different observational studies, mostly including a small number of patients, reported that adding adjunctive techniques (isolated or in combination) to RMA reduced significantly the prevalence of moderate or more IMR at follow-up compared to cases where RMA alone was used. 46,54,55,[58][59][60][61] A randomized controlled trial from CTS network compared RMA to MV replacement in case of severe IMR. 4,62 Results showed similar survival and LV remodeling, but patients with RMA had higher moderate or more IMR return (58.8% vs 3.8%) and higher heart failure-related events after a 2-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different observational studies, mostly including a small number of patients, reported that adding adjunctive techniques (isolated or in combination) to RMA reduced significantly the prevalence of moderate or more IMR at follow-up compared to cases where RMA alone was used. 46,54,55,[58][59][60][61] A randomized controlled trial from CTS network compared RMA to MV replacement in case of severe IMR. 4,62 Results showed similar survival and LV remodeling, but patients with RMA had higher moderate or more IMR return (58.8% vs 3.8%) and higher heart failure-related events after a 2-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…In selected cases, MV replacement has been proposed, in particular when IMR was severe. Different observational studies, mostly including a small number of patients, reported that adding adjunctive techniques (isolated or in combination) to RMA reduced significantly the prevalence of moderate or more IMR at follow‐up compared to cases where RMA alone was used 46,54,55,58‐61 . A randomized controlled trial from CTS network compared RMA to MV replacement in case of severe IMR 4,62 .…”
Section: Introductionmentioning
confidence: 99%